Cell metabolomics study on the anticancer effects of Ophiopogon japonicus against lung cancer cells using UHPLC/Q-TOF-MS analysis - Qiao Liu; Qiao Liu; Jia-Man Shen; Hui-Jie Hong; Qi Yang; Wen Liu; Zhong Guan; Yi-Tao Wang; Xiao-Jia Chen; Xiao-Jia Chen (Frontiers Media S.A., 2022)
Ophiopogon japonicus (OJ) is a traditional Chinese herbal medicine that has been used for thousands of years. Recently, the anticancer effects of OJ have been reported in multiple types of cancer, particularly in lung cancer. However, the underlying mechanisms remain unclear. In present study, the effects of OJ against NCI-H1299 human lung cancer cells were investigated, and the underlying mechanisms were explored using ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UHPLC/Q-TOF-MS)-based cell metabolomics. As a result, OJ inhibited the proliferation, induced the apoptosis and suppressed the migration of NCI-H1299 cells. A total of 22 differential metabolites responsible for the effects of OJ were screened and annotated based on the LC-MS-based cell metabolomics approach. The altered metabolites were involved in three metabolic pathways, including glycerophospholipid metabolism, ether lipid metabolism and glutathione metabolism. These results showed that cell metabolomics-based strategies are promising tools to discover the action mechanisms of OJ against lung cancer cells.